Monte Mozinho : a terra sigillata recuperada do sector B - Carvalho, Teresa Pires de (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The present text analyses the terra sigillata (red slip ware) appeared in a sector of Monte Mozinho’s site, from the first century. The particularity of this collection is that many of them are decorated peaces and probably belong to a spanish production from the almost unknown “Las Palmetas Pottery ware” ( ROMERO CARNICERO 1999: 169-208).